(untitled) (Indonesian Journal of Agrarian Law, 2024)
People with physical disabilities often face difficulties in carrying out their daily lives, especially in accessing disability-friendly public facilities. The BBRSPDF Prof. Dr. Soeharso Flats, built by the Ministry of Social Affairs, is a solution for people with physical disabilities by providing housing designed with accessibility principles. This study aims to explore the application of accessibility principles in the design and construction of the flats, as well as to evaluate the facilities provided to support the needs of people with physical disabilities. Using a normative legal research approach and a literature study method, this study explores various regulations related to accessibility and inclusive design, as well as evaluating facilities such as ramps, handrails, disabled toilets, and guiding blocks provided in the flats. The results of the study are expected to provide recommendations for further improvements in the design of more inclusive housing and support the independence of people with physical disabilities.